Biomarkers of Exposure among Adult Smokeless Tobacco Users in the Population Assessment of Tobacco and Health Study (Wave 1, 2013-14) - Cheng, Yu-Ching (Cancer Epidemiol Biomarkers Prev, 2020)
BACKGROUND: Monitoring population-level toxicant exposures from smokeless tobacco (SLT) use is important for assessing population health risks due to product use. In this study, we assessed tobacco biomarkers of exposure (BOEs) among SLT users from the Wave 1 (2013–14) of the Population Assessment of Tobacco and Health (PATH) Study. METHODS: Urinary biospecimens were collected from adults aged 18 and older. Biomarkers of nicotine, tobacco-specific nitrosamines (TSNAs), polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs), metals, and inorganic arsenic were analyzed and reported among exclusive current established SLT users in comparison to exclusive current established cigarette smokers, dual SLT and cigarette users, and never tobacco users. RESULTS: In general, SLT users (n=448) have significantly higher concentrations of biomarkers of exposure to nicotine, TSNAs and PAHs compared to never tobacco users; significant dose-response relationships between frequency of SLT use and biomarker concentrations were also reported among exclusive SLT daily users. Exclusive SLT daily users have higher geometric mean concentrations of total nicotine equivalent-2 (TNE2) and TSNAs than exclusive cigarette daily smokers. In contrast, geometric mean concentrations of PAHs and VOCs were substantially lower among exclusive SLT daily users than exclusive cigarette daily smokers. CONCLUSIONS: Our study produced a comprehensive assessment of SLT product use and 52 biomarkers of tobacco exposure. Compared to cigarette smokers, SLT users experience greater concentrations of some tobacco toxicants, including nicotine and TSNAs. IMPACT: Our data add information on the risk assessment of exposure to SLT-related toxicants. High levels of harmful constituents in SLT remain a health concern.